RESULTS OF THE STUDY ON THE PROCESS OF SELF- ACTUALIZATION AMONG ADOLESCENTS - Saipova Malaxat (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Annotation. The process of self-actualization in a teenager’s personality is complicated by age-related characteristics. In this context, the author, within the framework of his research, focused on the course of this process in adolescents growing up in families affected by labor migration. He also drew his own conclusions based on the research results presented in the table and diagram.